2020
DOI: 10.1002/pon.5598
|View full text |Cite
|
Sign up to set email alerts
|

Major depressive disorders in outpatients with cancers at the Nigerian National Hospital

Abstract: Objective Frequently, little attention is paid by clinicians on the psychiatric disorders that may be associated with cancers. The aim of this study was to determine the prevalence of major depressive disorders in outpatients with cancers at the Radiology Oncology Centre of the National Hospital, Abuja, Nigeria. It also sought to determine the socio‐demographic and clinical factors associated with the disorder. Method A sample of 177 randomly selected outpatients with cancers was interviewed with socio‐demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…To our knowledge, this study had reported lower prevalence estimate for major depressive disorder in the sub-Saharan Africa among patients living with cancer when compared with other reports in the region [9,17,[23][24][25][26][27]. However, the estimate was still high considering that depression increases the risk of mortality by 19% among patients living with cancer [13,17].…”
Section: Discussionmentioning
confidence: 66%
“…To our knowledge, this study had reported lower prevalence estimate for major depressive disorder in the sub-Saharan Africa among patients living with cancer when compared with other reports in the region [9,17,[23][24][25][26][27]. However, the estimate was still high considering that depression increases the risk of mortality by 19% among patients living with cancer [13,17].…”
Section: Discussionmentioning
confidence: 66%
“…The data in table 1 reveals that a total of 7 studies were investigated. 8,[14][15][16][17][18][19] The minimum sample size was 33, 14 while the maximum sample size was 222. 17 Research on the prevalence of depression among breast cancer patients in Nigeria began in 1998.…”
Section: Prevalence Of Depression Among Breast Cancer Patients In Nig...mentioning
confidence: 99%
“…17 Most of these studies were conducted in South-west Nigeria, [14][15][16][17][18] while two were carried out in Northcentral Nigeria. 8,19 In terms of research design, five of the selected articles 8,14-16,18 used a descriptive survey research design, one study 17 employed a comparative cross-sectional design, and one study 19 used a qualitative approach. The tools used for data collection in these selected articles were questionnaires and interviews.…”
Section: Prevalence Of Depression Among Breast Cancer Patients In Nig...mentioning
confidence: 99%
See 2 more Smart Citations